Green Human Resources Management Model in Achieving Corporate Sustainability at Sekolah Alam Al Fazza - Malau, Angelina Agustina; Nawangsari, Lenny Christina (Journal of Sustainable Economic and Business, 2025)
Objectives: The Sustainable Development Goals (SDGs) emphasize the importance of balancing economic, social, and environmental interests to achieve long-term sustainability. In education, managing human resources in an environmentally friendly manner through the implementation of Green Human Resources Management (GHRM) has become a key strategy to support corporate sustainability. This study aims to examine the implementation of the GHRM model in achieving sustainability at Sekolah Alam Al Fazza, which is committed to nature-based education and environmentally friendly practices.Methodology: The study employs a qualitative method with a case study approach, utilizing in-depth interviews, observations, and document analysis as data collection methods. Data were analyzed using NVivo 12 to identify and develop a relevant GHRM model.Finding: The results show that the implementation of GHRM at Sekolah Alam Al Fazza includes initiatives such as green recruitment, green training, and sustainability-based employee evaluations. However, the main challenges include limited infrastructure, lack of commitment, and unstructured evaluation indicators.Conclusion: To address these issues, the school adopts collaboration-based strategies and community empowerment through educational activities and environmental practices. This research contributes by providing a conceptual model to support school sustainability, while also highlighting the importance of aligning organizational policies.